Produksi dalam Ekonomi Islam: Antara Kebutuhan dan Tanggung Jawab Sosial - Renata Aulia Zahra; Navita Agraeni; Shinta Nabila Hendriana; Lina Marlina (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Islamic economics is an economic system based on the principles of the Qur’an and the Sunnah, with the aim of providing benefit (maslahah) for humanity. Conceptually, Islamic economics is fixed, but in practice, depending on certain situations and conditions, it may change or be applied more broadly. The main principles of Islamic economics consist of four elements: tawhid (monotheism), balance, freedom of will, and responsibility. Production is not only about creating goods from materials that do not exist, but also about producing goods that are useful and beneficial. The goal of production is to achieve happiness in both the worldly life and the hereafter, based on the principles of maqasid al-shariah. Production must be in accordance with Islamic values, so that it does not conflict with the protection of religion, life, intellect, lineage, and wealth. Production priorities should follow basic needs, secondary needs, and complementary needs, while taking into account justice and social aspects such as zakat and charity. Production must be carried out optimally, and the results should be distributed fairly among owners, managers, administrators, and workers. Factors of production such as natural resources, labor, capital, management, technology, and raw materials are also inseparable from the production process.